The Perfomance of Skewers Foundation Combined with Revetment under Rapid Drawdown Conditions on Balikpapan Coastal Area in Soft Soil using Numerical Analysis Undrained B - Sulardi; Tatag Yufitra Rus (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2022)
This research analyses the skewer foundation with Plaxis 2D considering the stability before and after drawdown conditions of the sea level with variations in the point load on the foundation. The study is carried out using the back-analysis method with the assumption that the protective building foundation is in a balanced state with the safety factor (SF) = 1.5. As a result, the stability of the rapid drawdown gave a different value which is the skewer foundation before rapid drawdown showed a better result of the performance of foundation during point load than after drawdown. Before drawdown conditions, the value of the point load (P) is 12 Tons. Meanwhile, after drawdown conditions, the skewer foundation is only able to accept a load of 5 tons. The value of the movement of the skewer foundation before and after the drawdown of sea-level conditions occurred at the same settlement value of about 0.0179 m = 1.18 cm. In this condition, the skewer foundation is considered capable of resisting the settlement issue where the maximum settlement value for shallow foundations for clay soils is not greater than 65 mm.